The role of ICT and mass media in post-disaster restoration and recovery progress: A case of the Great East Japan Earthquake - Hitoshi Mitomo; Tokio Otsuka; Stefan Y. Jeon; John W. Cheng (International Telecommunications Society (ITS), 2013)
The aim of this study is to investigate how the use of Information and Communication Technology (ICT) and mass media can motivate people in the disaster area to recover from the Great East Japan Earthquake with empirical data. Both ICT and mass media have played an important role after the disaster. While ICT has provided an effective way for information collection and dissemination, at the same time, the mass media has provided a reliable information source. Therefore, in order to examine the effects from the perspective of both the ICT and mass media, two different models are used. The first model examines the role of online civic participation driven by the use of ICT and mass media to see if it can create benefits offline from the perspective of social capital development. The second model investigates the effects of the use ICT and mass media on people's perception on the disaster and their intension on future recovery actions from the perspective of the cultivation theory from mass media studies.
Keywords: 330